Thymic lymphomas in Wistar rats exposed to N-methyl-N-nitrosourea (MNU) - Franchi, CAD; Bacchi, M. M.; Padovani, Carlos Roberto [UNESP]; de Camargo, JLV (Japanese Cancer Assoc, 2003)
The Brazilian Agency for the Environment (IBAMA) recently adopted an alternative medium-term multiple-organ assay system with the Wistar rat strain for detection of the carcinogenic potential of pesticides. Originally, this initiation-promotion protocol was established in Japan with the isogenic Fischer 344 male rat. Among the initiating agents used in that assay, N-methyl-N-nitrosourea (MNU) rapidly induces malignant lymphoma and leukemia and early mortality of rats from different strains. This study was developed to evaluate whether the outbred Wistar rats are also similarly susceptible to MNU. Particularly, it aimed to evaluate the dose-response relationship and to register the MNUinduced pre-neoplasia and neoplasia that may develop in the lympho-hematopoietic system (LHS) of the Wistar rat within a medium-term period. Four groups of male Wistar rats were treated during 2 weeks with vehicle or with MNU (80, 160 or 240 mg/kg body weight, i.p.). After sacrifice at the 12th and 20th weeks, the thymus, spleen, bone marrow, cervical and mesenteric lymph nodes and liver were collected for analysis. At the 20th week, LHS malignant tumors and benign vascular tumors occurred only in the high- and intermediate-dose MNU-treated animals. Four animals treated with 240 mg/kg developed diffuse thymic lymphomas; two others, treated respectively with 240 mg/kg and 160 mg/kg, developed spleen hemangiomas. The present observations indicate that the Wistar strain is as susceptible as other strains to the early development of MNU-induced LHS (pre)neoplasia. Therefore, this strain seems suitable to be used as test system in bioassay protocols that adopt MNU as an initiating agent for carcinogenesis.